If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4x + 3) = 12x + 4 + -4x + 2 Reorder the terms: 2(3 + 4x) = 12x + 4 + -4x + 2 (3 * 2 + 4x * 2) = 12x + 4 + -4x + 2 (6 + 8x) = 12x + 4 + -4x + 2 Reorder the terms: 6 + 8x = 4 + 2 + 12x + -4x Combine like terms: 4 + 2 = 6 6 + 8x = 6 + 12x + -4x Combine like terms: 12x + -4x = 8x 6 + 8x = 6 + 8x Add '-6' to each side of the equation. 6 + -6 + 8x = 6 + -6 + 8x Combine like terms: 6 + -6 = 0 0 + 8x = 6 + -6 + 8x 8x = 6 + -6 + 8x Combine like terms: 6 + -6 = 0 8x = 0 + 8x 8x = 8x Add '-8x' to each side of the equation. 8x + -8x = 8x + -8x Combine like terms: 8x + -8x = 0 0 = 8x + -8x Combine like terms: 8x + -8x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 3(2x-1)+2(x+3)=3(x-2)-2(x-1) | | x^2-13x+24=0 | | 12x-7=1+10x | | -7=-y+4 | | x+(x-3007)=7803 | | X=0+4 | | 250=84-5(x-4) | | 5+8q=7+7q | | -5y-3=1-6y | | X^2+x+0.21=0 | | 4(x-2)=x-8+3x | | 12x+6-10x=2x+6 | | (n-2)*5=20 | | 22a+5-(a-7)=48 | | x(x-2)+(x-2)(x+2)=0 | | 2-.75k=.125k+9 | | 4(x+2)=5-(x+2) | | 10(9c-1)-14=88c+10 | | 3x+-3+5=5 | | 4(x+2)=5-(x-2) | | 0.6(x-2)=12.0 | | 8x+8-5x=3x+8 | | 7n=77 | | 12x-3=90+3(x-7) | | n-12=10 | | 3x+4=6-7x | | 10x^2+1=11X | | -5(n+3)-(7+8n)= | | 2(e-15)=32 | | 3x(-3x+5)=5 | | 37x+20=0 | | x(2-x)(2+x)-x-2= |